Intraocular Inflammation Associated with New Therapies for Cutaneous Melanoma – Case Series and Review - Fierz, F. C.; Meier, F.; Chaloupka, K.; Böni, C. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background. In advanced cutaneous melanoma, new systemic therapies include immunotherapy by checkpoint inhibition and targeted inhibition of the mitogen-activated protein kinase pathway; these are becoming increasingly well established. We describe the clinical presentation of uveitis in three patients with concomitant systemic melanoma treatment.History and Signs. Three patients with metastatic melanoma receiving systemic therapy (ipilimumab, vemurafenib) presented at our institution with a short history of ocular symptoms. Clinical findings included anterior uveitis, intermediate uveitis, disc swelling, inflammatory choroidal lesions and retinal vasculitis.Therapy and Outcome. All three patients responded well to local and/or systemic steroid treatment. In one case, the systemic anti-cancer drug was discontinued after the onset of uveitis.Conclusions. Ocular inflammation may occur in the setting of systemic melanoma therapy. Presentations of uveitis include Vogt-Koyanagi-Harada-like syndromes. Ocular inflammation can usually be controlled by topical and sometimes systemic corticosteroid therapy. However, treatment guidelines are not established and management of these patients demands close cooperation with the oncologist.
Keywords: ocular side effects; uveitis; intraocular inflammation; Vogt-Koyanagi-Harada; ipilimumab; vemurafenib; CTLA-4-inhibition; BRAF-inhibition; immune-related adverse events